Facile synthesis of magnetically separable CoFe2O4/Ag2O/Ag2CO3 nanoheterostructures with high photocatalytic performance under visible light and enhanced stability against photodegradation - Šutka, Andris; Döbelin, Nicola; Joost, Urmas; Smits, Krisjanis; Kisand, Vambola; Maiorov, Mihael; Kooser, Kuno; Kook, Mati; Duarte, Roberto Felix; Käämbre, Tanel (Elsevier Sci Ltd., 2017)
We have developed magnetically separable and reasonably stable visible light active photocatalysts containing CoFe2O4 and mixture of Ag2O/Ag2CO3 nanoheterostructures. Obtained ternary nanoheterostructures outperform previously reported magnetically separable visible light photocatalysts, showing one of the highest visible light photocatalytic dye degradation activities in water by a magnetically separable photocatalyst. Photocatalytically active part is Ag2O/Ag2CO3 whereas the CoFe2O4 mainly has stabilizing and magnetic separation functions. The Ag2CO3 phase junction on Ag2O nanoparticle surface were obtained by straightforward phase transformation from silver oxide to silver carbonate in air due to ambient CO2. The phase transformation was followed using X-ray diffraction (XRD), and hard X-ray photoelectron spectroscopy (HAXPES) measurements.
Riga Technical University supported the preparation of this manuscript from the Scientific Research Project Competition for Young Researchers No. ZP-2016/7. The authors wish to kindly acknowledge the financial support of HZB, Estonian Research Council (PUT1096, PUT735 and IUT2-25) and Estonian Centre of Excellence in Research Project “Advanced materials and high-technology devices for sustain-able energetics, sensorics and nanoelectronics” TK141 (2014–2020.4.01.15-0011).
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Silver oxide; Silver carbonate; Photocatalytic; Nanoheterostructures; Magnetic